Answer:
y = (1/3)x + 13/3
Explanation:
1. Find the slope (m)
slope = change in y divided by change in x
m=
![(y_(2)-y_(1) )/(x_(2)-x_(1) ) = (6-4)/(5-(-1)) = (2)/(5+1) = (2)/(6) = (1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/1r7txcd4hp1e5c6gmlf32epd8lpgwni4zk.png)
2. Subsitute 1/3 for m and pick one point to plug into y =mx+b
Ex: (5, 6) -> y= 6 x = 5
6 = 1/3(5) + b
3. Simplify: 6 = 1/3(5) + b
6 = 5/3 + b
4. Solve for b (isolating the variable) by adding 1/3 to both sides
6 - 5/3 = 5/3 - 5/3 + b
5. Simplify: 6 - 5/3 = 5/3 - 5/3 + b
18/3 - 5/3 = b -> 13/3 = b
5. plug in 13/3 for b and 1/3 for m in y = mx + b
y = mx + b -> y = (1/3)x + 13/3